The trend forecast model in the achievement of energy security of the countries and regional complexes - Stanojević, Petar (Sociološki pregled, 2022)
The paper describes and illustrates a simple, robust, yet sufficiently detailed model that ensures quick and accurate enough forecast of trends and their possible effect on the processes related to energy security and, accordingly, global security. The heuristic model also takes into account diversity in the understanding of the energy paradigm. It is based on the 4Аs definition of energy security (Acceptability, Availability, Affordability, Accessibility) and uses the regional security complex theory. It considers four factors of the first and twenty-three factors of the second level. The created model enables considering the factors that are difficult to measure, which makes the forecast comprehensive. The model is applied in the cases of the EU, Serbia and China. The conclusion is that a set of factors acting towards the reduction of energy security of the countries whose strategic aspiration is the “green paradigm” exceeds by far the number of those with positive effects. The results point to the conclusion that China should continue the current energy strategy. The actual application of the model, through the analysis of influential factors, indicates the problems that will have their security-related repercussions. The factors that need to be treated as priorities have been singled out if the actual situation needs improvement for the purpose of increasing and maintaining energy security of a country or a regional complex.